2018
DOI: 10.1371/journal.pone.0209832
|View full text |Cite
|
Sign up to set email alerts
|

Role of granulocyte transfusions in combating life-threatening infections in patients with severe neutropenia: Experience from a tertiary care centre in North India

Abstract: Bacterial and fungal infections still remain an important cause of mortality in patients with hematological malignancies and in recipients of hematopoietic stem cell transplants (HSCT) especially in developing countries like India. Granulocyte transfusions (GTX) from healthy donors may lead to early clearance of index infection and thus prevent mortality. The aim of the present study was to evaluate the efficacy of GTX in combating life-threatening infections and preventing mortality in patients of hematologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 40 publications
3
23
1
3
Order By: Relevance
“…12 In another study, it has been observed that patients receiving median doses of 1.5-3.0 × 10 8 granulocytes/kg had reduced infection-related mortality. 13 Also, Garg et al 14 demonstrated in their study that doses >10 × 10 8 / kg though associated with a higher total leucocyte count (TLC) increment at 6 hours post-infusion had no significant impact on survival at 30 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In another study, it has been observed that patients receiving median doses of 1.5-3.0 × 10 8 granulocytes/kg had reduced infection-related mortality. 13 Also, Garg et al 14 demonstrated in their study that doses >10 × 10 8 / kg though associated with a higher total leucocyte count (TLC) increment at 6 hours post-infusion had no significant impact on survival at 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…The infection-related survival was 82.4% while overall survival (OS) was 77% at day 30. 17 Garg et al 14 also analyzed the efficacy of granulocyte therapy in combating life-threatening infections in patients of hematological disorders/ recipients of hematopoietic stem cell transplant (HSCT) with severe neutropenia. A total of 143 granulocyte transfusions in 60 patients were included.…”
Section: Discussionmentioning
confidence: 99%
“…So erzielten Teofili et al die besten Ergebnisse mit einer Konzentration von 1,5-3 × 10 8 Zellen/kg Körpergewicht, während sie bei einer darüber hinausgehenden Zellzahl sogar einen Anstieg der Sterblichkeit verzeichneten [51]. Die Gruppe um Garg et al schlägt ein Plateau des maximal erreichbaren Effekts bei einer Konzentration von 5 × 10 9 Zellen pro transfundierter Einheit vor [52]. Ein weiterer zu berücksichtigender Faktor ist die Art der Infektion, unter der ein Patient leidet.…”
Section: Stand Der Evidenz Von Granulozytentransfusionenunclassified
“…B. im Gewebe, besser mit GKs therapieren lassen als eine Sepsis [53]. Die Ansprechraten decken sich dabei mit den Zahlen von Garg et al [52]. Prinzipiell ist die Wirksamkeit davon abhängig, in welchem Ausmaß die transfundierten Immunzellen unterschiedliche Infektionsorte erreichen.…”
Section: Stand Der Evidenz Von Granulozytentransfusionenunclassified
See 1 more Smart Citation